Effectiveness of the ring house strategy in collecting and developing visual thinking - Waleed Abd, Ismael Rhman; Huseen Faraj, Alaa; Khaleel Ibraheem, Mohammed (Opción, 2019)
The present study aims to identify the effectiveness of the Circular House strategy on the achievement and development of visual thinking among student in the preparatory stagy in the Holy Quran and Islamic Education .The research assumed the two hypotheses: 1-There is no significant statistical difference at the level of (0.05) between the average scores of students in the experimental group and the average score of students in the control group in the overall test attributed to effecti- veness of the Circular House strategy in the Holy Quran and Islamic Educa- tion as a teaching method compared with the traditional metho 2-There is no significant statistical difference at the level of(0.05) between the average scores of students of the experimental group and the average score of students in the control group in the visual thinking attributed to effectiveness of the Circular House strategy in Holy Quran and Islamic Education as a teaching method compared with the traditional method. The sample of study consisted of (49)students divided to(25)students in the experimental group who studied using the Circular House strategy and (24)students in the control group studied in the traditional method .To achie- ve the research goal,preparing the post-test consisted of (30)paragraph and the pre and the post test of the visual thinking consisted of(20)paragraph the result showed that there was a statistically significant difference between the two averages in the achievement test for scores of the students of two research groups and for the experimental group. There was also a statistica- lly significant difference between the mean difference for the test scores. Of the visual thinking skills of pre and post test for two groups of research and for the experimental group.